Pembelajaran Ekonomi Efektif di Madrasah Aliyah Sahid - Asnan Purba; Maturidi Maturidi (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
This study aims to explore ways of effective economic learning in Madrasah Aliyah Sahid, given the importance of effective learning to produce outputs that are expected in accordance with the expectations of Madrasah Aliyah Sahid. In this study the researchers tried to find what steps were taken by the teacher to create effective learning specifically economic lessons both from the methods used by the teacher, the learning model how it was implemented in MA Sahid and how the evaluation was carried out at this institution, and the driving factors, inhibiting factors in effective economic learning activities at Madrasah Aliyah Sahid. Keywords: economics, learning, effective, madrasa